Unveiling FDA-approved Drugs and Formulations in the Management of Bladder Cancer: A Review - Bansal, Keshav; Chaudhary, Neeraj; Bhati, Hemant; Singh, Vanshita (Current Pharmaceutical Biotechnology, 2025)
Urological cancers are one of the most prevalent malignancies around the globe. Specifically, bladder cancer severely threatens the health of humans because of its heterogeneous and aggressive nature. Extensive studies have been conducted for many years in order to address the limitations associated with the treatment of solid tumors with selective substances. This article aims to provide a summary of the therapeutic drugs that have received FDA approval or are presently in the testing phase for use in the prevention or treatment of bladder cancer. In this review, FDA-approved drugs for bladder cancer treatment have been listed along with their dose protocols, current status, pharmacokinetics, action mechanisms, and marketed products. The article also emphasizes the novel preparations of these drugs that are presently under clinical trials or are in the approval stage. Thus, this review will serve as a single point of reference for scientists involved in the formulation development of these drugs.
Keywords: clinical trials